(4-2х)+(5х-3)=(х-2)-(х+3)

0 голосов
86 просмотров

(4-2х)+(5х-3)=(х-2)-(х+3)


Алгебра (15 баллов) | 86 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(4-2х)+(5х-3)=(х-2)-(х+3)

4-2х+5х-3=х-2-х-3

(-2х+5х)+(4-3)=(х-х)(-2-3)

3х+1=-5

3х=-5-1

3х=-6

х=-6:2

х=-2                                                  

(4-2·(-2))+(5·(-2)-3)=(-2-2)-(-2+3)  (это проверка)

(4+4)+(-10-3)=(-4)-(1)

8-13=-4-1

-5=-5

(172k баллов)
0 голосов

4-2х+5х-3=х-2-х-3

1+3х=-5

3х=-5-1

3х=-6

х=-6:2

х=-2

Ответ: -2

 

(70 баллов)